Event reconstruction in ACTAR TPC: Adaptation for transfer experiments - Lozano-González Miguel; Fernández-Domínguez Beatriz; Lois-Fuentes Juan; Roger Thomas (EPJ Web of Conferences, 2023)
Preliminary results of the performance of the RANSAC algorithm over data measured with the ACTAR TPC detector are herewith presented. With the aim of improving track reconstruction in highly contaminated events, an initial assessment of the algorithm is given for elastic reactions involving p, d with a beam of 20O. Results show great possibilities for data/noise discrimination, which in the near future will be extended to small angle and more energetic events, which are key for transfer reactions.